"Could You, Would You, Should You?" Regulating Cross-Border Travel Through COVID-19 Soft Law in Finland. (9th March 2021) - KORKEA-AHO, Emilia; SCHEININ, Martin
Abstract : In the coronavirus pandemic that has swept the world, the Finnish Government, like many of its peers, has issued policy measures to combat the virus. Many of these measures have been implemented in law, including measures taken under the Emergency Powers Act, or by ministries and regional and local authorities exercising their legal powers. However, some governmental policy measures have been implemented using non-binding guidelines and recommendations. Using border travel recommendations as a case study, this article critically evaluates governmental soft law-making. The debacle over the use of soft law to fight the pandemic in Finland revealed fundamental misunderstandings about the processes and circumstances under which instruments conceived as soft law can be issued, as well as a lack of attention to their effects from a fundamental rights perspective.